2014
DOI: 10.1103/physrevd.89.043006
|View full text |Cite
|
Sign up to set email alerts
|

Dirac dynamical resonance states around Schwarzschild black holes

Abstract: Recently, a novel kind of scalar wigs around Schwarzschild black holes-scalar dynamical resonance states were introduced in [Phys. Rev. D 84, 083008 (2011)] and [Phys. Rev. Lett. 109, 081102 (2012)]. In this paper, we investigate the existence and evolution of Dirac dynamical resonance states. First we look for stationary resonance states of a Dirac field around a Schwarzchild black hole by using the Schrödinger-like equations reduced from the Dirac equation in Schwarzschild spacetime. Then Dirac pseudo-stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…This means that ultralight scalar field can be very long-lived around the GMGHS black hole. Similar results have been found for massive scalar and Dirac fields around a Schwarzschild or a Reissner-Nordström black hole [17,22,23].…”
Section: Matching the Two Solutionsupporting
confidence: 85%
See 1 more Smart Citation
“…This means that ultralight scalar field can be very long-lived around the GMGHS black hole. Similar results have been found for massive scalar and Dirac fields around a Schwarzschild or a Reissner-Nordström black hole [17,22,23].…”
Section: Matching the Two Solutionsupporting
confidence: 85%
“…Quasibound states of a black hole have been studied under several different conditions [13][14][15][16][17][18][19][20][21][22][23]. The minimal extension of general relativity, i.e., the dilatonic gravity or called scalar tensor theory, can be traced back to Kluza-Klein compactification and Dirac's large number hypothesis, in which only one new degree is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4], Barranco et al studied the evolution of massive scalar fields around a Schwarzschild BH and found configurations that can survive for a very long time, even for cosmological time scales. Zhou et al further showed that such long-lived nontrivial distributions can be extended to Dirac fields [5]. These dynamical resonance solutions are basically described by the so-called quasibound states of massive fields in the BH spacetimes, which have attracted much attention in recent years [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of the results in Refs. [3][4][5] is that the long-lived modes are obtained in the limit of smallmass coupling M µ ≪ 1, where M and µ are the masses of the BH and field, respectively. There is a simple physical explanation for this: smaller value of M µ corresponds to weaker gravitational attraction between the external field and BH, which implies that it takes a longer time for the BH to absorb the external fields around it.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the possibility of describing the dark matter in the galactic halo by the coherent excitation of an ultra-light scalar field [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], including the supermasive black hole [51][52][53][54], in previous work we analyzed the time scale for the quasi-bound states on a supermassive, nonrotating black hole background [32,33]; see [55] for a recent generalization to the Dirac field. In particular, we showed in Ref.…”
Section: Introductionmentioning
confidence: 99%